Press & media coverage - Mohd Samsi, Mohd Shafik; Kamaruddin, Siti Faridah; Joseph, Stefanie Natasha Rich; Robert, Cindy; Jafri, Fakhira; Jeri, Shirley Clare; Juhari, Nur Nadia Qausar (Corporate Communication Unit, UiTM Mukah Campus, 2025)
The achievement of UiTM Sarawak Kampus Mukah branch featured in the press & media coverage reflects the institution's excellence in academics, innovation, and community engagement. This media recognition strengthens the campus's role as a key driver of educational development in central Sarawak and enhances UiTM'S national reputation.